Crisis communication planning and strategies for nonprofit leaders - Haupt, Brittany; Azevedo, Lauren (New York, NY : Routledge, 2023)
"Crisis Communication Planning and Strategies for Nonprofit Leaders examines the unique position of nonprofit organizations in an intersection of providing public services and also being a part of emergency management practices. This text discusses the evolution of crisis communication planning, the unique position of nonprofit organizations and the crises they face, along with provision of conceptual and theoretical frameworks to generate effective crisis communication plans for nonprofit organizations to utilize within diverse crises. Through the use of innovative real-life case studies investigating the impact of crisis communication plans, this book provides the foundational knowledge of crisis communication planning, theoretically supported strategies, crisis typology, and planning resources. Each chapter focuses on critical strategic planning concepts and includes a summary of key points, discussion questions, and additional resources for each concept. With this text, nonprofit organizations will be able to strategically plan for organization-specific and emergency management related crises, develop effective crisis communication plans, garner internal and external support, and generate assessment strategies to maintain the relevancy of these plans within their future endeavors. Crisis Communication Planning and Strategies for Nonprofit Leaders offers a new and insightful approach to crisis communication planning to assist nonprofit organizations that are called upon to fulfill a variety of community needs, such as sheltering, food distribution, relief funding, family reunification services, volunteer mobilization and much more. It will be an essential resource for nonprofit organizations"--
Nonprofits and Crises -- Crisis Communication and Management -- Crisis Communication Theories and Strategies -- Governance Strategies and Leadership during Crises -- Preparing for Crisis Communication Planning -- The Crisis Communication Plan and Strategy Development Communication with Internal and External Stakeholders -- Implementing the Crisis Communication Plan -- Evaluation and Assessment Strategies -- Looking Back and Moving Forward: Adapting the Crisis Communication Plan -- Case Studies.
Keywords: Communication in crisis management; Nonprofit organizations -- Management; POLITICAL SCIENCE / Public Affairs & Administration